Iterative Development of an Online Dietary Recall Tool: INTAKE24 - Emma Simpson (Nutrients, 2017)
Collecting large-scale population data on dietary intake is challenging, particularly when resources and funding are constrained. Technology offers the potential to develop novel ways of collecting large amounts of dietary information while making it easier, more convenient, intuitive, and engaging for users. INTAKE24 is an online multiple pass 24 h dietary recall tool developed for use in national food and nutrition surveys. The development of INTAKE24 was a four-stage iterative process of user interaction and evaluation with the intended end users, 11–24 years old. A total of 80 11–24 years old took part in the evaluation, 20 at each stage. Several methods were used to elicit feedback from the users including, ‘think aloud’, ‘eye tracking’, semi-structured interviews, and a system usability scale. Each participant completed an interviewer led recall post system completion. Key system developments generated from the user feedback included a ‘flat’ interface, which uses only a single interface screen shared between all of the various activities (e.g., free text entry, looking up foods in the database, portion size estimation). Improvements to the text entry, search functionality, and navigation around the system were also influenced through feedback from users at each stage. The time to complete a recall using INTAKE24 almost halved from the initial prototype to the end system, while the agreement with an interviewer led recall improved. Further developments include testing the use of INTAKE24 with older adults and translation into other languages for international use. Our future aim is to validate the system with recovery biomarkers.